OP0124 Contextualising quality of life in ANCA associated vasculitis (AAV). (23rd January 2014) - Basu, N.; McClean, A.; Luqmani, R.; Harper, L.; Flossmann, O.; Jayne, D.; Little, M.; Amft, E.N.; Dhaun, N.; McLaren, J.; Kumar, V.; Erwig, L.; et al.
Abstract : Background: Impaired quality of life (QOL) is of universal relevance and not just confined to the unhealthy. Although existing data demonstrates poor QOL amongst patients with AAV, it is essential to contextualise these reports with both general and other diseased populations in order to fully ascertain the scale of the problem. Thus far, studies have only made retrospective comparisons with unmatched populations using different methodologies. Furthermore, study sample sizes have been sufficient to quantify only the largest of differences. Objectives: This large study aimed to quantify QOL in AAV patients compared to matched general and disease control populations. Methods: A multi-centre case-control study using two groups of a) population and b) disease controls. AAV cases were recruited from rheumatology and renal departments across the UK. For each participating case, general population controls were identified from a commercial on-line sampling frame (>80% population coverage). They were matched according to age, sex and postcode. In addition, disease controls were invited, matched according to age, sex and department. Cases recruited from rheumatology departments were matched to patients with inflammatory arthritis while those recruited from renal departments were matched to patients with non-inflammatory chronic kidney disease, reflecting a typical clinic attendee from the respective specialty. All cases and controls completed a questionnaire which combined recognised measures of QOL. Specific instruments assessed physical and mental health status (SF36), sleep disturbance (Estimation of sleep problems questionnaire) and fatigue (Chalder Fatigue Scale).The scores of these were dichotomised into high and low categories by the mean of the population controls. In addition, anxiety and depression was defined using the Hospital Anxiety and Depression Scale (HADS) and data collected on employment status. Cases were compared to controls using conditional logistic regression and results expressed as odds ratios (OR). Results: 410 cases were identified from 11 centres, with 470 population and 318 disease controls. Cases reported significantly poorer QOL than population controls across all domains. Compared to controls, cases were substantially more likely to report low physical and mental health respectively (OR 7.0, 95%CI 4.4-11.1 and OR 2.5, 95%CI 1.7-3.6). In addition they were much more likely to be unemployed due to their health (OR 6.9, 95%CI 3.0-15.8), report high fatigue (OR 4.1, 95%CI 2.7-6.3), feel depressed (OR 4.3, 95%CI 2.4-7.5), endure sleep disturbance (OR 2.1, 95%CI 1.5-2.9) and suffer anxiety (OR 1.6, 95%CI 1.1-2.3). Across all domains, cases reported no significant differences in QOL compared to disease controls. Conclusions: Compared with the general population, AAV patients experienced significantly impaired QOL. QOL levels were as poor as those reported by typical rheumatology and renal clinic attendees whose considerable needs are already well established. Disclosure of Interest: None Declared